(+/-)-7alpha,8beta-dihydroxy-9beta,10beta-epoxy-7,8,9,10-tetrahydrobenzo(a)-pyrene is an intermediate in the metabolism and binding to DNA of benzo(a)pyrene. - King, H W (1976)
The addition of borate buffer to the aqueous methanol used to elute hydrocarbon-deoxyribonucleoside derivatives from an LH 20 Sephadex column resulted in the separation of the products of reaction with DNA of the stereoisomers, (+/-)7alpha,8beta-dihydroxy-9alpha,10alpha-epoxy- and (+/-)-7alpha,8beta-dihydroxy-9beta,10beta-epoxy-7,8,9,10-tetrahydrobenzo(a)pyrenes, i.e., the syn- and anti-benzo(a)pyrene-diolepoxide, respecitvely. By this technique it was shown that the microsome-mediated binding to DNA of benzo(a)pyrene-7,8-dihydrodiol involved exclusively the anti-benzo(a)pyrene-diolepoxide. The benzo(a)pyrene binding to DNA that resulted on exposure of BHK21/C13 cells to this carcinogen was also shown to result predominantly by reaction of the anti-benzo(a)pyrene-diolepoxide. However, in this case other derivatives, including the syn-benzo(a)pyrene diolepoxide, might also be involved.